2023
DOI: 10.3389/fendo.2022.1039079
|View full text |Cite
|
Sign up to set email alerts
|

T4 rather than TSH correlates with BMD among euthyroid adults

Abstract: PurposeThe objective of this study was to evaluate the association between thyroid hormone and bone mineral density (BMD) among euthyroid adults.MethodsThis cross-sectional study researched the information from the National Health and Nutrition Examination Survey 2007–2010. We included 3,759 euthyroid participants finally. We used multivariate linear regression models to evaluate the linear relationship between the thyroid hormone profile and BMD. Subgroup analyses stratified by gender and age were further per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…According to Sheng et al, TSH showed no significant correlation with BMD of euthyroid adults and was also not associated with the variations of BMD and the fracture risk in the elderly [ 29 ]. A similar study by Lin et al yielded consistent results and suggested thyroid hormone, particularly T4, as a more appropriate indicator between bone and thyroid function, demonstrating weak negative correlations between T4 and BMD [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Sheng et al, TSH showed no significant correlation with BMD of euthyroid adults and was also not associated with the variations of BMD and the fracture risk in the elderly [ 29 ]. A similar study by Lin et al yielded consistent results and suggested thyroid hormone, particularly T4, as a more appropriate indicator between bone and thyroid function, demonstrating weak negative correlations between T4 and BMD [ 30 ].…”
Section: Discussionmentioning
confidence: 99%